Incidere, Incidere, Incidere Giorgio Trentin tra etica dell'arte e impegno politico - Sbordone, Giovanni (Carte, Studi e Opere - Centro Trentin di Venezia, 2015)
Giorgio Trentin (1917-2013), eldest son of the anti-fascist exile Silvio and brother of the unionist Bruno, was one of the greatest connoisseurs, enthusiasts and 'defenders' of engraving art in Italy. With this conference promoted a few months after his death, the Academy of Fine Arts of Venice and the Centro documentazione e ricerca Trentin have brought together the researches of scholars from different backgrounds and the testimonies of those who knew Giorgio Trentin. The aim was the one of restoring unity to the two 'faces' of his figure: on one hand the civil and anti-fascist militancy (a characteristic and unmistakable mark of the family) on the other the commitment in the artistic field, which represented personal space of Giorgio or, better, his personal declination of that common militancy. To him, in fact, the engraving technique was an indispensable paradigm of moral rigour and the search for truth.